2016
DOI: 10.1093/bja/aev548
|View full text |Cite
|
Sign up to set email alerts
|

Physical properties and functional alignment of soft-embalmed Thiel human cadaver when used as a simulator for ultrasound-guided regional anaesthesia

Abstract: The soft-embalmed Thiel cadaver is a highly durable simulator that has excellent physical and functional properties that allow repeated injection for intensive ultrasound-guided regional anaesthesia training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 26 publications
0
36
0
1
Order By: Relevance
“…used sonoelastography to study the interstitial, intra-arterial, and intraneural spread of local anesthetics in Thiel cadavers and found that these can be used for objective assessment of the learning. [827] These cadavers can also be used for testing new technology and developing new techniques in UGRA. [5]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…used sonoelastography to study the interstitial, intra-arterial, and intraneural spread of local anesthetics in Thiel cadavers and found that these can be used for objective assessment of the learning. [827] These cadavers can also be used for testing new technology and developing new techniques in UGRA. [5]…”
Section: Discussionmentioning
confidence: 99%
“…There is literature available on the use of Thiel cadavers for learning UGRA but the technique is still not developed in India. [345678] Recently, cadaver training and research facility was setup in our center and one of our co-authors (SL) gained experience in preparation of Thiel cadaver.…”
Section: Introductionmentioning
confidence: 99%
“…For example, more than half of DCIAs clearly originated distal to the inguinal ligament and their presence should be considered during USG‐FNB performed around the inguinal ligament. The accurate identification, detection rate, and visualization pattern of the arterial branch from the femoral artery superficial to the femoral nerve around the inguinal ligament on the ultrasound image need to be warranted by future studies using Thiel embalmed cadavers; these are appropriate for ultrasound examination (Benkhadra et al, ; Desroches et al, ; Munirama et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Cadaveric models for regional anesthesia have mostly been developed with the aim of improving the visualization of anatomical structures and the needle. 20 Among the many models, Thiel embalmed cadavers are known to provide the best physical and functional properties for peripheral nerve blocks 21,22 and perhaps should be validated to evaluate interfascial plane blocks.…”
Section: Anatomical Studies On Interfascial Plane Blocks: Extrapolatementioning
confidence: 99%
“…Les modèles cadavériques pour l'anesthésie régionale ont principalement été mis au point afin d'améliorer la visualisation des structures anatomiques et de l'aiguille. 20 Parmi les nombreux modèles, les cadavres embaumés selon la technique de Thiel sont réputés fournir les meilleures propriétés physiques et fonctionnelles pour les blocs des nerfs périphériques 21,22 et devraient donc peut-être être validés pour évaluer les blocs de plans interfasciaux.…”
Section: é Tudes Anatomiques Sur Les Blocs De Plans Interfasciaux : Punclassified